K-180 G Micro Gas Turbine Performance Evaluation / Mohamad Zulfazli Arief Abd Latif...[et al.] - Abd Latif, Mohamad Zulfazli Arief; Ahmad, Muhammad Aiman; Mohd Nasir, Rizal Effendy (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The K-180 G jet turbine is categorized as turbojet engine. This paper studied and analyzed the performance of K-180 G micro jet turbine for Unmanned aerial Vehicle (UAV) at static condition. The project was done to study thrust and temperature behavior with respect to rpm for a turbojet engine using standard kerosene fuel. A theoretical thermodynamic model was derived to understand theoretical aspect behind the test and to ensure the validity of performance measured. Various sensors were integrated to the gas turbine and computed to record the performance parameters such as EGT, thrust, engine rpm and pump power. The engine was tested several times in order to obtain average reading. At maximum RPM, the average thrust recorded was 18.57 kg, the maximum temperature recorded was 523˚C and the maximum pump power was 293 W. The relationship between thrust against RPM and the thrust against pump power is third order polynomial and thrust against EGT is parabolic. The mass flow rate of fuel was obtained from the relationship of the RPM against pump power which is third order polynomial. The thermodynamic theoretical model validated the engine's performance measured with the percentage error between 1 to 30%.